1997
DOI: 10.1063/1.119848
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced luminance in polymer composite light emitting devices

Abstract: We demonstrate that mixing insulating oxide nanoparticles into electroluminescent polymer materials results in increased current densities, radiances, and power efficiencies in polymer light emitting diode devices. For low driving voltages, an order of magnitude increase in current density and light output is achieved with minimal loss in device lifetime. At 5 V, we achieve radiances of 10 000 cd/m 2 with external quantum efficiencies ϳ1% for nanoparticle/MEH-PPV composite films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
108
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 223 publications
(129 citation statements)
references
References 11 publications
(14 reference statements)
18
108
1
Order By: Relevance
“…Similar phenomena obtained for nanohybrid layers were explained due to the TiO 2 /polymer boundaries causing differences in band gap between oxide nanoparticles and the conjugate polymer [17]. Based on these results we take an explanation for the improved performance which supports the suggestion by Carter et al [16]. It is suggested by the change in device morphology caused by the incorporation of nanoparticles into the solution.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Similar phenomena obtained for nanohybrid layers were explained due to the TiO 2 /polymer boundaries causing differences in band gap between oxide nanoparticles and the conjugate polymer [17]. Based on these results we take an explanation for the improved performance which supports the suggestion by Carter et al [16]. It is suggested by the change in device morphology caused by the incorporation of nanoparticles into the solution.…”
Section: Resultssupporting
confidence: 77%
“…For instance, in [15] the authors attributed this enhancement to stimulated emission of optically-pumped MEH-PPV films when TiO 2 particles were embedded in. Whereas, in [16] by their obtained results the author indicates that no evidence of line narrowing or changes in the line shape are observed at different voltages implying that the mechanism for improved performance is distinctly different from that found in optically-pumped TiO2/MEH-PPV films. The authors concluded that optical scattering phenomenon is not causing the increase in performance.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…These results indicate that the Aucapped TiO 2 nanocomposite incorporated in the EL polymer facilitates the increase in charge carriers by roughness assisted tunneling, as reported by Park et al 15 It is believed that the nanocomposite adhere to the ITO anode by electrostatic forces; thereby, the nanomorphologically roughened EL layer causes a larger interfacial contact area between the cathode ͑Ca͒ and EL polymer that can be responsible for the enhanced electrical performance of HPLED. 8,16 Moreover, the nanocomposite adhered on the ITO layer behaves like field emitters and thus the charges are gathered around the sharp clusters of nanocomposite. The charges can easily tunnel into the MEH-PPV EL layer facilitating a current flow into HPLED.…”
Section: -mentioning
confidence: 99%
“…6,7 This goal was realized by blending the electron transporting nanoparticles into luminescent polymers, thereby enhancing performance without use of complicated structures. 8 The purpose of the present study was to increase the brightness of HPLED by using hybrid nanocomposite polymer systems. We employed titanium oxide ͑TiO 2 ͒ capped with gold ͑Au͒, which has potential for use in energy-conversion devices.…”
mentioning
confidence: 99%